The Influence of the Gojek Application Rating on Customer Trust of Mie Gacoan Ngaliyan: Pengaruh Rating Aplikasi Gojek Terhadap Kepercayaan Pelanggan Mie Gacoan Ngaliyan - Afin Mursida, Muhammad; Kusuma Wardani, Devi; Tiyas Apriliani, Awaliyah; Dewi Fitriana, Eka; Zikrinawati, Khairani; Fahmy, Zulfa (Journal of Multidisciplinary Science, 2024)
Some people buy something without looking at the rating, so this study aims to see whether Mie Gacoan Ngaliyan's customer trust grows from seeing ratings on the Gojek application or there is already customer trust in the Mie Gacoan brand. This study uses explanatory quantitative research methods by analyzing using a simple linear regression test. The sample in this study was 72 people in the Ngaliyan area who were selected using a purposive sampling technique. The scale used is Likert and Guttman. The rating variable obtained an average yes answer of 62.46%, which means that customers have satisfaction with Mie Gacoan so this can affect customer trust in the Gojek application. The results of the regression test show that the rating has a positive effect of 20.8% and is significant on trust. customers of the Gojek application. The regression coefficient for this variable is 2.421 which means that the assessment variable has a positive factor on the trust variable. Ratings on Mie Gacoan have an influence on purchases made by customers on the Gojek application.